2011
DOI: 10.1111/j.1537-2995.2011.03217.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemolysis and red blood cell mechanical fragility in shed blood after total knee arthroplasty

Abstract: The washing device returned more Hb to the patients relative to the amount of free Hb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Mechanical shear stress associated with washing has been shown previously to cause a sublethal injury to RBCs and increased in vivo hemolysis after transfusion with subsequent release of CFH and iron. 30,31 Although exposure to saline during the wash may contribute to increased cell fragility, the washed cells are immediately resuspended in standard preservative solution. We postulate that the "older" more fragile cells are lost during the washing process and the cells that remain are more susceptible to lysis than before washing, especially after 42 days of storage.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical shear stress associated with washing has been shown previously to cause a sublethal injury to RBCs and increased in vivo hemolysis after transfusion with subsequent release of CFH and iron. 30,31 Although exposure to saline during the wash may contribute to increased cell fragility, the washed cells are immediately resuspended in standard preservative solution. We postulate that the "older" more fragile cells are lost during the washing process and the cells that remain are more susceptible to lysis than before washing, especially after 42 days of storage.…”
Section: Discussionmentioning
confidence: 99%
“…Washing is efficient at reducing the free hemoglobin content. Rates of clearance have been reported to be between 53% and 99%, with the concentration of free hemoglobin in the washed product ranging from 1.0 to 30.4 mg/mL 52–56 …”
Section: Washingmentioning
confidence: 99%
“…In a recent study exploring the fragility of cell salvaged blood, washed and unwashed post total knee arthroplasty, it was demonstrated that there was more haemolysis and damage in the washed group compared with the unwashed group as shown by a higher free Hb and higher mechanical fragility index. Washed blood, similar to methods we have used in our institution had a total free Hb dose of 0·55 g but this was not statistically different ( P = 0·615) when compared with unwashed ones (Ley et al , ).…”
Section: Discussionmentioning
confidence: 76%
“…Free Hb is a scavenger of nitric oxide (NO) irreversibly binding to and reducing levels. NO is a regulator of smooth muscle tone and platelet activation and acts as a vasodilator in the microcirculation (Rother et al, 2005;Ley et al, 2012). Reduced NO levels result in vasoconstriction, systolic and diastolic blood pressure (BP) increases, reduced tissue oxygenation, smooth muscle dystomies, gastrointestinal (GI) contractions, endotheliac dysfunction and platelet aggregation with increased thrombotic events (Rother et al, 2005;Sloan et al, 2009;Kelleher et al, 2011;Vermeulen Windsant et al, 2012).…”
mentioning
confidence: 99%